Transforming Breast Cancer Together: European elections manifesto 2019 seizing the opportunities for breast cancer patients. (December 2019) - Cardoso, Fatima; Bușoi, Cristian-Silviu; Cattaneo, Ivana; Decise, Donatella; Cardone, Antonella; Filicevas, Alex; Gentile, Elena; Wierinck, Lieve; Knox, Susan; Sebastiani, Silvia; Terrasanta, Carole; Ujupan, Sonia; et al.
Abstract: With the European Parliament elections having taken place in May 2019 and a new European Commission (EC) taking office in November 2019, this year is critical for European policymakers, as goals and priorities of the European Union (EU) for the next five years will be discussed and agreed upon. This Manifesto issued by the Transforming Breast Cancer Together initiative calls upon policymakers to improve services for patients in an area still of high unmet need and reduce the societal impact of breast cancer by elevating it as a health policy priority to improve breast cancer prevention, diagnosis and care across Europe.